COMPARISON OF SILODOSIN AND TAMSULOSIN IN THE MEDICAL EXPULSION THERAPY OF MID AND LOWER URETERIC STONES (Journal of Medical & Health Sciences Review, 2025)
Background: Medical expulsive therapy (MET), which is widely used to treat ureteric stones, is practiced mainly with alpha-blockers such as silodosin and tamsulosin. However, further work evaluating silodosin as a ureteric stone passage promoter has revealed promising results and has hinted at its merits in efficacy and safety profile over that of alpha blocker tamsulosin. Objective: To compare the efficacy and safety of silodosin and tamsulosin in the expulsion management of mid and lower ureteric stones. Methodology: A total of 100 patients with a mid and a lower ureteric stone were randomly allocated to use either silodosin (8 mg once daily) or tamsulosin (0.4 mg once daily). The stone expulsion rate and mean expulsion time, along with pain episodes, need for additional analgesia, and adverse effects were assessed as main outcomes, while other relevant clinical outcomes were regarded as secondary outcomes. SPSS was used for statistical analysis, and a p-value less than 0.05 was considered significant.Results: Silodosin showed a higher stone expulsion rate as compared to tamsulosin (86% vs 70%), and mean expulsion time was significantly reduced with silodosin (11.2 ± 3.2 vs. 12.9 ± 4.5 days; p = 0.032). The number of pain episodes was lower in the silodosin group (3.5 ± 1.3 vs. 4.2 ± 1.6; p = 0.018). Nevertheless, silodosin was associated with a significantly greater incidence of retrograde ejaculation (24% vs.8%, p=0.029) and dry ejaculation (20% vs. 6%, p=0.037).Conclusion: Silodosin has a higher incidence of ejaculatory dysfunction but is more effective than tamsulosin in reducing the number of pain episodes that occur during the expulsion of ureteric stones. Therapy should be selected for the individual patient according to patient preferences and clinical considerations.